Evaluation of Fertility Rate in the Couples after Uterine Septum Resection - Mansoureh Vahdat; Samaneh Rokhgireh; Elahe Afshari; Samaneh Mohammadpour; Mohammad Ali Hosseini (Men's Health Journal, 2019)
Introduction: Uterine septum is one of the most common congenital abnormalities in women that leads to numerous gynecological problems and adverse obstetrics outcomes. This study aimed to evaluate the effects of Hysteroscopic Resection on pregnancy outcomes in women undergone the surgery.